2013
DOI: 10.1186/1471-2253-13-31
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical analysis of blood and urine in the course of acute kidney injury in critically ill patients: a prospective, observational study

Abstract: BackgroundSequential physicochemical alterations in blood and urine in the course of acute kidney injury (AKI) development have not been previously described. We aimed to describe these alterations in parallel to traditional renal and acid–base parameters.MethodsOne hundred and sixty eight consecutive critically ill patients with no previous kidney disease, who had an indwelling urinary catheter at ICU admission and who remained with the catheter for at least two days without dialysis were included. A sample o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 36 publications
3
40
1
4
Order By: Relevance
“…Unfortunately, we don't have the data regarding intra-operative fluid management and the types of fluids used. Although fluctuations in urinary values are expected in a 24-h period, we believe, based on recent publications, 5,13,19 that a single spot urine biochemistry assessment per day, usually at the same hour (together with the routine blood exams) is useful and quite more practical than in a 24-h urine sample.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Unfortunately, we don't have the data regarding intra-operative fluid management and the types of fluids used. Although fluctuations in urinary values are expected in a 24-h period, we believe, based on recent publications, 5,13,19 that a single spot urine biochemistry assessment per day, usually at the same hour (together with the routine blood exams) is useful and quite more practical than in a 24-h urine sample.…”
Section: Discussionmentioning
confidence: 91%
“…We have previously suggested that some of these parameters may be useful in the early AKI diagnosis. 5,13,14 However, in these studies, most AKI diagnoses were made at ICU admission, limiting the data available at the days preceding AKI. In the present study, we have found that a minority of the patients had AKI diagnosed at ICU admission (D0), which is not surprising in a population composed mainly by elective surgical patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nesse contexto, tem-se observado a avaliação dos eletrólitos urinários para esse propósito, com estudos clínicos demonstrando um padrão específico na fase precoce da injúria renal aguda, como a diminuição na excreção urinária de sódio e cloreto (13). Adicionalmente, índices derivativos dos eletrólitos urinários, como a fração de excreção urinária de sódio e ureia, também tem sido utilizados como ferramentas potenciais para distinguir a injuria renal aguda entre estrutural e funcional, com potencial impacto na sua duração (14,15).…”
Section: Lista De Abreviaturasunclassified